Review of criteria and process for green procurement / Mohammad Hassan Khairil Anuar, Natasha Khalil and Asmah Alia Mohamad Bohari - Khairil Anuar, Mohammad Hassan; Khalil, Natasha; Mohamad Bohari, Asmah Alia (2021)
The construction industry inevitably plays a vital role in Malaysia's economic growth; however, it can harm environmental aspects. Green procurement initially helps to reduce the environmental issues in construction by considering green products and sustainable materials for construction. However, the procurement process in construction is relatively complex as it involves many activities and various stakeholders. This study investigates the criteria for construction works needed to implement green projects inMalaysia's construction sector. Through extensive literature reviews and focusedgroup discussions (FGD), the criteria were established. The FGD was used to get a better and more likely result as the participants are experts in the field. The participants mainly consisted of experts in green and sustainable construction projects. The process was divided into phases; i.e.; i) inception or planning phase, ii) design phase, iii) tendering phase, iv) construction phase, and v) operation phase. It was found that the project's green requirements should be initiated clearly in the planning phase from clients. The findings help to depict more precise guidance in adopting green procurement to achieve aims in green construction.